ILLOCUTIONARY ACTS IN THE FIRST DEBATE OF JAKARTA GOVERNOR ELECTION 2017 - Maeda Elsera Siagian; Rahmad . Husein; Sahron . Lubis (LINGUISTIK TERAPAN, 2021)
ABSTRACTIn communication, sometimes people get difficulties in interpreting the messages. In communication, sometimes other people have difficulty interpreting the implied message of a word or sentence. The meaning of utterances does not depend on the literal meaning uttered by the speaker, but there is an implicit meaning behind the social speech and action in which the speech occurs. Searle (2014) state Illocutionary act the five basic kinds of illocutionary acts are namely assertive, directive, commissive, expressive and declarative. The objectives of this study are to explain types of illocutionary acts in first debate of Jakarta Governor election 2017. Bogdan and Biklen (1992:29) add that qualitative research is descriptive where data collected are in the form of word and picture rather than number. Research design in this study was conducted by descriptive qualitative research. Data analysis in this research is there are 733 clauses of which illocutionary act in the first debate of Jakarta governor election 2017. the technique for collecting data is documentary technique which download video from Youtube and transcribed the video into the interactive model by using Miles and Huberman (2014) with the three phases of data analysis such as data condensation, data display and conclusion. The findings show all types of illocutionary act were used in the first debate of Jakarta governor election 2017, namely: assertive (54%), directive (15%), commissive (18%), expressive (12%) and declarative (1%). Assertive dominantly is used in Governor and vice governor in the form of stating out of 250 utterances or 34,1%.  Keywords: Illocutionary act, Speech, Governor, Jakarta, Debat